Comprehensive analysis of circRNAs from cashmere goat skin by next generation RNA sequencing (RNA-seq) - Zheng, Yuanyuan (Sci Rep, 2020)
Circular RNA (circRNA) is endogenous non-coding RNA (ncRNA) with a covalently closed circular structure. It is mainly generated through RNA alternative splicing or back-splicing. CircRNA is known in the majority of eukaryotes and very stable. However, knowledge of the circRNA involved in regulating cashmere fineness is limited. Skin samples were collected from Liaoning cashmere goats (LCG) and Inner Mongolia cashmere goats (MCG) during the anagen period. For differentially expressed circRNAs, RNA sequencing was performed, and the analysis led to an identification of 17 up-regulated circRNAs and 15 down-regulated circRNAs in LCG compared with MCG skin samples. In order to find the differentially expressed circRNAs in LCG, we carried out qPCRs on 10 candidate circRNAs in coarse type skin of LCG (CT-LCG) and fine type skin of LCG (FT-LCG). Four circRNAs: ciRNA128, circRNA6854, circRNA4154 and circRNA3620 were confirmed to be significantly differential expression in LCG. Also, a regulatory network of circRNAs-miRNAs was bioinformatically deduced and may help to understand molecular mechanisms of potential circRNA involvement in regulating cashmere fineness.